Characterization of topography hidden under paint by means of qualitative algorithms robust to the number of frames and non-uniform illumination. (November 2022) - Baradit, E.; Avendaño, M.; Cañas, G.; Yañez, M.; Trivi, M.; Cariñe, J.
Highlights: In this work, hidden topography under paint were characterized by dynamic speckle image processing. The choice of an algorithm for dynamic speckled image processing was made with the lighting profile in mind. The results show that the performance of various intensity normalized speckle algorithms decreases with the number of frames used. Abstract: The use of qualitative algorithms in images with dynamic speckle allows generating a three-dimensional intensity map, which correlates with the sample activity. Samples in an evaporation state will present temporary mobility related to their volume, which allows characterizing their topography. However, the quality of the topographic characterization depends on the illumination profile and the number of images or frames used. In this paper, a review of various qualitative processing algorithms is carried out in order to evaluate their robustness to the number of frames and their dependence on the beam profile, evaluating the characterization of topography hidden by a layer of paint in process of drying. We use an aluminum structure with perforations of different diameters and depths as a sample. Among the algorithms used, we highlight the results obtained by the normalized DJC method, which characterizes the topography of our sample with a correlation of 0.98 and presents stability to the number of frames used. Thus, with these results we validate the use of dynamic speckle in the characterization of a surface covered with paint.